Forms of sharenting as a modern social phenomenon of children’s portrait - Novaković, Uroš (Sociološki pregled, 2026)
The paper analyzes the parents’ contemporary practice of posting virtual content about their children on social networks and online platforms in general. Sharing content about a child on social networks and online without restrictions is an approach that fully recognizes the parents’ right and freedom to shape the visibility of their child, as well as the child’s right to privacy. Even limiting access to one’s own profile to a certain close circle of people does not guarantee absolute protection of the child’s well-being. Namely, the danger of closed profiles, to which only “friends” or close people, relatives, godparents of the child have access, is reflected in the fact that these people can further forward, or download, such content. Initially, the concept of sharenting was associated with sharing content about children for altruistic motives, and then for exclusively personal, entertaining, non-profit motives of parents, and the further “evolution” of this phenomenon was in the direction of parents sharing children-related content for business motives. Sharing content about children for the sake of parents’ entertainment motives is the leading reason why content about children is shared online.
Keywords: social networks; sharing with restrictions; sharing without restrictions; non-profit sharenting; profit sharenting